2021
DOI: 10.1016/j.ajic.2021.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Environmental hygiene, knowledge and cleaning practice: a phenomenological study of nurses and midwives during COVID-19

Abstract: Background Environmental cleanliness is a fundamental tenet in nursing and midwifery but often overshadowed in practice. This study explored nurses’ and midwives’ knowledge and experiences of infection prevention and control (IPC) processes and cleaning, and perceptions about workplace risk-management during COVID-19. Methods Six registered and enrolled nurses (one with dual midwife qualifications) were recruited. In-depth telephone interviews were analysed using Colaiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This finding is supported by the previous study, argued that health education about controlling and preventing the spread of disease, and increasing awareness about the reliability of personal protective equipment, could improve nurses' performance [7]. Further, also believed that it is necessary to emphasize the clinical and dynamic nature in increasing critical insight among nurses into infection prevention control (IPC) efforts, including time, staff knowledge, adherence to health protocols, work procedures, hospital facilities, organizational/hospital context, and environmental hygiene in order to preventing and controlling the COVID-19 infection [18]. Furthermore, the results of this study are also in line with reported that 76.8% of nurses had adequate preparedness in dealing with the COVID-19 patients [19], but in contrast to the study revealed that only 45.3% of the nurses were adequately prepared to care the COVID-19 patients [11], and also showed that the overall preparedness of nurses in dealing with COVID-19 is moderate level [20].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the previous study, argued that health education about controlling and preventing the spread of disease, and increasing awareness about the reliability of personal protective equipment, could improve nurses' performance [7]. Further, also believed that it is necessary to emphasize the clinical and dynamic nature in increasing critical insight among nurses into infection prevention control (IPC) efforts, including time, staff knowledge, adherence to health protocols, work procedures, hospital facilities, organizational/hospital context, and environmental hygiene in order to preventing and controlling the COVID-19 infection [18]. Furthermore, the results of this study are also in line with reported that 76.8% of nurses had adequate preparedness in dealing with the COVID-19 patients [19], but in contrast to the study revealed that only 45.3% of the nurses were adequately prepared to care the COVID-19 patients [11], and also showed that the overall preparedness of nurses in dealing with COVID-19 is moderate level [20].…”
Section: Discussionmentioning
confidence: 99%
“…Questioning symptoms using the Center for Disease Control and Prevention’s COVID-19 symptom list is also seen as a preventable method for transmission (Cohen et al 2021 ; CDC 2020 ). In addition, measures such as the frequency of cleaning, disinfectants to be used, and personal protective measures to be followed during use are other factors that reduce contamination (World Health Organization 2020b ; Curryer et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is not enough to be equipped with knowledge about infection prevention and control, and health workers must be able to implement and comply with infection prevention and control efforts (Ashinyo et al 2021;Alhumaid et al 2021). Apart from implementing infection prevention and control when providing services to patients, health workers must also participate in the cleanliness of the room and environment of healthcare facilities (Curryer et al 2020). In addition, the patient must also carry out involvement in infection prevention and control efforts (Agreli et al 2019).…”
Section: Introductionmentioning
confidence: 99%